A case of near-drowning: are safety standards in sports adequate? - Senanayake, M. P.; Ajanthan, R.; Aluthge, P. (Sri Lanka College of Paediatricians, 2002)
Childhood is the ideal time for encouragement of sports because physical activity levels and patterns, once established, last into adult life 1,2. Injuries will occur but are often minor and do not warrant hospital
Keywords: sport adequate; safety standard; ideal time; adult life; physical activity level